Network Organization in Health and Disease: On Being a Reductionist and a Systems Biologist Too - Bechtel, W. (Pharmacopsychiatry, 2013)
Whereas the challenge for traditional mechanistic science was to identify parts and operations, the current challenge in many fields of biology is to understand how the many parts of mechanisms are organized in networks and their operations coordinated across these networks. This paper explores how tools from graph theory are enabling analysis of organization at both macro- and micro-levels. In applying these approaches to brain regions, systems neuroscientists are identifying both small-world organization with hubs at the macro-scale and frequently occurring subgraphs that link specific brain regions at a more micro-scale. This has lead to the discovery of networks in which activity in multiple brain regions exhibits coherent oscillations and demonstrations that these networks are disrupted in various mental disorders.·
Keywords: mechanistic explanation; dynamical systems theory; dynamic mechanistic explanation; graph theory; small worlds; subgraphs; mental disorders